The CTBT controversy : different perceptions in South Asia - Ahmar, Moonis (Karachi : Dept. of International Relations, University of Karachi, 2000)
Papers read at a seminar.
Machine generated contents note: Legal and Conceptual Dimensions of the CTBT -- Ahmer Bilal Soofi -- The International Dimensions of the CTBT -- Shaista Tabassum -- The CTBT Controversy: The Regional Dimension -- Moonis Ahmar -- CTBT and Public Perceptions in Pakistan -- Arshi Saleem Hashmi -- The CTBT and the Isolationist Agenda -- Pervez Hoodbhoy -- CTBT: A Tool for American Domination -- Tarik Jan -- The CTBT Controversy: -- Need for a Consensual Approach -- Kamal Matinuddin -- The Future of Nuclear Non-Proliferation -- in South Asia -- Ghulam Umer -- The CTBT Controversy: The Role of -- Nuclear Nationalism and Religious Extremism -- S. MutahirAhmed -- The Economic Dimensfon of the -- CTBT Controversy -- Farhan H. Siddiqui -- Nuclear Explosions and Environmental -- Degradation: CTBT as a Case Study -- Naeem Ahmed -- A Chronological Survey of CTBT: 1996-2000 -- Nausheen Wasi -- Index.
Includes bibliographical references and index.
Keywords: Nuclear weapons -- Testing -- Law and legislation -- South Asia; Nuclear arms control -- South Asia